2021
DOI: 10.1038/s41467-021-26004-5
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial chromosomal mobility via lateral transduction exceeds that of classical mobile genetic elements

Abstract: It is commonly assumed that the horizontal transfer of most bacterial chromosomal genes is limited, in contrast to the frequent transfer observed for typical mobile genetic elements. However, this view has been recently challenged by the discovery of lateral transduction in Staphylococcus aureus, where temperate phages can drive the transfer of large chromosomal regions at extremely high frequencies. Here, we analyse previously published as well as new datasets to compare horizontal gene transfer rates mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 59 publications
1
35
0
1
Order By: Relevance
“…Experimental studies have found that different types of MGEs vary in their rates of transfer between bacterial cells. In particular, in vitro rates of transfer of phage have been found to be several orders of magnitude higher than of transposons ( Humphrey et al, 2021 ). A 16-day in vivo study of MGE dynamics for two strains of CC398 also observed variation in the mobility of MGEs: the Tn 916 transposon, the type V SCC mec and an φSa3 prophage were all stably maintained and not horizontally transferred, while other prophages and plasmids were both gained and lost by daughter cells ( McCarthy et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies have found that different types of MGEs vary in their rates of transfer between bacterial cells. In particular, in vitro rates of transfer of phage have been found to be several orders of magnitude higher than of transposons ( Humphrey et al, 2021 ). A 16-day in vivo study of MGE dynamics for two strains of CC398 also observed variation in the mobility of MGEs: the Tn 916 transposon, the type V SCC mec and an φSa3 prophage were all stably maintained and not horizontally transferred, while other prophages and plasmids were both gained and lost by daughter cells ( McCarthy et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that the higher number of DE genes in strain Newman could be an emergent property off competition between phage K and the resident prophages. Chen et al ( 45 ) showed that the induced pac -type phages φNM1, φNM2, and φNM4 of strain Newman facilitate amplification of the host DNA flanking the prophage, which could lead to horizontal gene transfer by lateral transduction ( 46 , 47 ). Moreover, the temperate phages play a key role in the spread of the SaPIs ( 48 , 49 ) and the generalized transduction of other mobile genetic elements ( 50 , 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies have found that different types of MGEs vary in their rates of transfer between bacterial cells. In particular, in vitro rates of transfer of phage have been found to be several orders of magnitude higher than of transposons (Humphrey et al 2021). A 16-day in vivo study of MGE dynamics for two strains of CC398 also observed variation in the mobility of MGEs: the Tn 916 transposon, the type V SCC mec and an ϕSa3 prophage were all stably maintained and not horizontally transferred, while other prophages and plasmids were both gained and lost by daughter cells (McCarthy et al 2014).…”
Section: Discussionmentioning
confidence: 99%